Pharmacokinetic analysis of an extended-pulsed fidaxomicin regimen for the treatment of Clostridioides (Clostridium) difficile infection in patients aged 60 years and older in the EXTEND randomized controlled trial. (20th January 2020) - Guery, Benoit; Georgopali, Areti; Karas, Andreas; Kazeem, Gbenga; Michon, Ingrid; Wilcox, Mark H; Cornely, Oliver A
Abstract: Background: Fidaxomicin is a recommended treatment for Clostridioides difficile infection (CDI) and reduces CDI recurrence incidence versus vancomycin. An extended-pulsed fidaxomicin (EPFX) regimen further reduces recurrence frequency. However, the pharmacokinetic profile of fidaxomicin in an EPFX regimen is unknown. Objectives: To evaluate plasma and stool concentrations of fidaxomicin and its metabolite, OP-1118, after EPFX administration for CDI. Methods: In the Phase 3b/4 EXTEND trial, patients aged ≥60 years with toxin-confirmed CDI were randomized to receive EPFX (oral fidaxomicin twice daily, Days 1–5; once daily on alternate days, Days 7–25). Fidaxomicin and OP-1118 concentrations were determined using post-dose plasma samples obtained on Days 5 ± 1, 12 ± 1 and 25/26, and post-dose stool samples obtained on Days 5 ± 1, 12 ± 1 and 26 ± 1. Results: Plasma samples from 14 patients were included in the pharmacokinetic analysis; 12 of these patients provided stool samples. Median (range) plasma concentrations of fidaxomicin on Day 5 ± 1 and Day 25/26 were 0.0252 (0.0038–0.1220) mg/L and 0.0069 (0–0.0887) mg/L, respectively, and those of OP-1118 were 0.0648 (0.0142–0.3250) mg/L and 0.0206 (0–0.3720) mg/L, respectively. Median (range) stool concentrations of fidaxomicin and OP-1118 on Day 26 ± 1 were 272.5 (0–524) mg/kg and 280.5 (0–1120) mg/kg, respectively. Conclusions: EPFX treatment maintained fidaxomicin stool concentrations above the C. difficile MIC90 until Day 26 ± 1. Systemic exposure to fidaxomicin and OP-1118 was low throughout and there was no evidence of accumulation in plasma or stool during treatment.